Exact Solutions for Generalized Klein-Gordon Equation - Yang, Libo; Wang, Daoming; An, Fengxian (Journal of Informatics and Mathematical Sciences, 2012)
The Modified$(\frac{G}{G'})$-expansion method is used to solve the Generalized Klein-Gordon equation, by means of the method, three types of exact traveling wave solutions are obtained, including the hyperbolic functions, trigonometric and rational function solutions. In this method, $G$ is general solution of a second order linear ODE, so the method is direct, simple; more importantly, this method can be used in many other nonlinear evolution equations to obtain traveling wave solutions. This will have a good sense to promote the broad application of Klein-Gordon equation.